Financing of MSE by foreign banks in India - Rengasamy, Dhanuskodi (South Asian Academic Research Journal, 2012)
ABSTRACT Foreign banks are available in myriad in India and known for offering snug service in all parts of the country. Banks exposure under MSE sector has shown a significant growth during the financial year 2009-2010 and 2010-2011 precisely, the sector grew by 59.72 per cent and 33.56 per cent respectively. The research paper compacted with financing of MSE sector by foreign banks in India, RBI policy for promoting MSE sector and the notifications of MSMED Act, 2006 for the progress of MSE in India. The research paper deeply analyzed the role of foreign banks in the development of MSE by credit assistance. Further the study investigated the relationship between MSE advances and loans & advances and priority sector advances of the foreign banks in India. It is found that growth rate and trend of MSE advances by foreign bank in India were positive. The share percentage of SME advances in loans & advances and priority sector were positive and progress. Further the study found that through correlation matrix, the independent factors of loans & advances and priority sector advances have positive correlation with MSE advances during the sturdy period.